Changes in Climate and Land Use Over the Amazon Region: Current and Future Variability and Trends - Marengo, Jose A.; Souza, Carlos M.; Thonicke, Kirsten; Burton, Chantelle; Halladay, Kate; Betts, Richard A.; Alves, Lincoln M.; Soares, Wagner R. (Frontiers in Earth Science, 2018)
This paper shows recent progress in our understanding of climate variability and trends in the Amazon region, and how these interact with land use change. The review includes an overview of up-to-date information on climate and hydrological variability, and on warming trends in Amazonia, which reached 0.6-0.7 °C over the last 40 years, with 2016 as the warmest year since at least 1950 (0.9 °C +0.3°C). We focus on local and remote drivers of climate variability and change. We review the impacts of these drivers on the length of dry season, the role of the forest in climate and carbon cycles, the resilience of the forest, the risk of fires and biomass burning, and the potential “die back” of the Amazon forests if surpassing a “tipping point”. The role of the Amazon in moisture recycling and transport is also investigated, and a review of model development for climate change projections in the region is included. In sum, future sustainability of the Amazonian forests and its many services requires management strategies that consider the likelihood of multi-year droughts superimposed on a continued warming trend. Science has assembled enough knowledge to underline the global and regional importance of an intact Amazon region that can support policymaking and to keep this sensitive ecosystem functioning. This major challenge requires substantial resources and strategic cross-national planning, and a unique blend of expertise and capacities established in Amazon countries and from international collaboration. This also highlights the role of deforestation control in in support of policy for mitigation options as established in the Paris Agreement of 2015.